NEED ANALYSIS OF ENGLISH TEXTBOOKS BASED ON THE ADDIE MODEL - Arin Inayah; Tri Mulyati (Universitas Islam Nahdlatul Ulama Jepara, 2021)
This research is research and development on the development of English textbooks for non-English department using ADDIE model, however this research only the first phase of ADDIE model, which is analysis. This research only describing the process and analyzing toward English textbooks need which is used in teaching and learning to non-English learners. This research uses descriptive qualitative research method, because the data analysis in the form of word. The researcher use three instrument to get the data, they are: questionnaire forgetting deep information of the student need, interview to know the teaching and learning process doing by the lecturer, and documentation to know the learners outcomes in learning English, especially English for general basic courses in the university. Based on research finding and discussion, students purpose in learning English are to be able to speak English in interest with their work, English level of the students are beginner, they understand simple sentence in daily conversation, students’ needs and wishes according with English learning are their English skill can support their academic competence and also their work, students need according with material and assignment is basic material for beginner learners with completed by the assignment, students need according with activities in the classroom is that they want to have active activity by solving the problem in pairs or small group. Based on the interview of the English lecture, the researcher concludes that the students are enthusiastic in the teaching and learning process, Learning method which is used is lecture method and cooperative learning, mastery of the material is still lacking, the average of students skill is at the beginner level. The material which is should be mastered by students are focusing on reading and speaking, read the English literature and English article. Focus on answering the question by correct speaking. For the micro skills, they have to memorize many vocabularies and doing correct practicing in pronounces the word. Based on document analysis, the researcher concludes that: The students are able to translate the text related to their department, the students are able to explain the reading technique of the scientific text to know the information of the text, the students are able to improve speaking skill with correct sentences and other learning outcomes deal with the English lecture.